The Effectiveness of Transcranial Magnetic Stimulation for Obsessive-Compulsive Disorder - De Vera, Patricia (MacEwan University Student eJournal, 2024)
Obsessive-compulsive disorder (OCD) is an anxiety-related disorder. Obsessions are experienced as recurring, unwanted thoughts. In response to obsessions, people feel driven to act with repetitive behaviours, known as compulsions. Obsessions and compulsions cause significant distress and impairment in an individual’s daily life and relationships. OCD is relatively common, with a lifetime prevalence rate between 2%-3%. Thus, research must find an effective treatment for individuals with OCD. This paper examines a relatively new area of research that explores the use of transcranial magnetic stimulation (TMS) to treat OCD. TMS is a non-invasive brain stimulation that has recently shown promising effects in treating psychological disorders. Studies researching TMS on OCD, primarily with individuals who have not responded to previous treatments, have found it to be effective, with symptoms significantly decreasing post-treatment, and with effects lasting up to 3-months post-treatment. Overall, TMS appears to offer an effective alternative for individuals with treatment-resistant OCD. However, while studies on TMS show significant results, participants with greater OCD symptoms and/or sleep disturbances tend to report a decreased response to treatment. Also, studies using TMS typically have limitations with their sample sizes, lack of control groups, and lack of long-term follow-up assessments. Overall, TMS appears to be effective for OCD, but future research needs to address current limitations to determine the true effectiveness of this new treatment.